If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 = 7 + -1x Solving -11 = 7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -11 + x = 7 + -1x + x Combine like terms: -1x + x = 0 -11 + x = 7 + 0 -11 + x = 7 Add '11' to each side of the equation. -11 + 11 + x = 7 + 11 Combine like terms: -11 + 11 = 0 0 + x = 7 + 11 x = 7 + 11 Combine like terms: 7 + 11 = 18 x = 18 Simplifying x = 18
| 45g+7=-6 | | x^3-(2x^2)+1.25x-0.25=0 | | 1952-7abc+18=62 | | 2+2k=8k+3-6k | | x^3-(2x^2)+1.5x-0.25=0 | | 5n-8=n+27 | | [9(y+5)-17]-[3(y-4)+3]= | | 5x-3+7x=45 | | 2+2k=8k+3-6 | | 2(x-2)=3x-4x+5 | | 2x+10=6x-4 | | 7-3(3)=-3+1 | | 17.50-8.75= | | (n+4)-(-3n-7)= | | k/15-13=4 | | 7k^2-54k-16= | | [7(z+5)-17]+[3(z-2)+2]= | | 19abc+18=62 | | 3t=3r-54 | | 12x-10-12=0 | | 10=4x+x^2 | | m=25(i) | | 5y+y-3=6y-5+6 | | 19abc=62 | | -6-(4-(2*4-(4-3)))= | | (n-4)-(-3n-7)= | | 2v^2+v-36= | | 1[1-7(2-6)]= | | 19abc*b=62 | | 49-14=5(x-5) | | x^2-14x+44=-4 | | 12(x+9)=-180 |